Not merely the absence of disease : twelfth general programme of work 2014-2019 adopted by the World Health Assembly in May 2013 (World Health Organization GenevaCH, 2014)
Provides a high-level strategic vision for the work of WHO. Establishes priorities and provides an overall direction for the six-year period commencing in January 2014.
Keywords: WHO